Theoretical approaches about the role of electoral advertising in a context of political malaise - Fierro Zamora, Pedro (2017)
We are going to develop a theoretical frame to understand the role that campaigns would have in a context of political malaise. Considering the multidimensionality of the discontent, we are going to conceive the disaffection like the component more related with what Putnam & Goss called ‘the previous conditions for an effective democracy’. Taking into account the results of other studies surrounding the democratic effects of the campaigns, we will suggest that the electoral advertising could help us to improve the civic sense of the citizens from an attitudinal dimension, strengthening our democracies.